2022
DOI: 10.3390/ma15186260
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Iron Extraction from Low-Grade Siderite via a Conveyor Bed Magnetization Roasting–Magnetic Separation Process: Kinetics Research and Applications

Abstract: Upgrading and utilizing low-grade iron ore is of great practical importance to improve the strategic security of the iron ore resource supply. In this study, a thermal analysis–infrared (IR) analysis–in-situ IR method was used to investigate the reaction mechanism and kinetics of Daxigou siderite. Experiments were conducted using a conveyor bed magnetization roasting process (CBMRP) to investigate the magnetization of siderite. Multi-stage magnetic separation processes were adopted to extract magnetite. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The iron mineral transformation pattern, reaction kinetics, and magnetic separation of siderite by magnetization roasting have been systematically investigated in previous studies [2][3][4][5]. These results confirmed that siderite could be efficiently magnetized by calcination at 600-800 • C for 3-10 s in a reducing atmosphere, and magnetite could be effectively collected by the multiprocess weak magnetic separation method [7,[11][12][13]. Existing studies have confirmed the feasibility and advantages of suspended-state magnetization roasting technology (e.g., fast reaction, good magnetization effect, mature process equipment, etc.).…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…The iron mineral transformation pattern, reaction kinetics, and magnetic separation of siderite by magnetization roasting have been systematically investigated in previous studies [2][3][4][5]. These results confirmed that siderite could be efficiently magnetized by calcination at 600-800 • C for 3-10 s in a reducing atmosphere, and magnetite could be effectively collected by the multiprocess weak magnetic separation method [7,[11][12][13]. Existing studies have confirmed the feasibility and advantages of suspended-state magnetization roasting technology (e.g., fast reaction, good magnetization effect, mature process equipment, etc.).…”
Section: Introductionsupporting
confidence: 61%
“…Extensive technical research and development confirmed that the Daxigou iron ore has a considerable development value; however, successful large-scale industrial production has not yet been achieved [5,6]. A process system was developed for the magnetization roasting of siderite based on suspended-state calcination technology, and a 10,000-ton pilot plant was built for this purpose [7]. As this technology is crucial to the comprehensive utilization of siderite, conducting research on pilot-scale process technology is necessary to apply it industrially [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations